PPh3-Mediated [3+2] Cycloaddition Reaction between Bis-Substituted Allenoate and N-Tosylaldimines to Construct 2-Pyrrolines - Kong, Xiangwen; Liu, Lihua; Luo, Siqin; Fan, Shilu; Qian, Haisheng; Xiao, Hua (Synlett, 2018)
A triphenylphosphine-promoted [3+2] cycloaddition of α,γ-bis-substituted allenoates and N-tosylaldimines followed by alkene isomerization was disclosed, affording a series of functionalized 2-pyrroline derivatives in moderate chemical yields with random diastereoselectivities.
Keywords: nucleophilic catalysis; allenoate; cycloaddition; triphenylphosphine; 2-pyrroline